2022
DOI: 10.3390/cancers14133079
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNAs in Thyroid-Follicular-Cell-Derived Carcinomas

Abstract: Among the thyroid neoplasias originating from follicular cells, we can include well-differentiated carcinomas, papillary (PTC) and follicular (FTC) thyroid carcinomas, and the undifferentiated anaplastic (ATC) carcinomas. Several mutations in oncogenes and tumor suppressor genes have already been observed in these malignancies; however, we are still far from the comprehension of their full regulation-altered landscape. Even if only 2% of the human genome has the ability to code for proteins, most of the noncod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 153 publications
0
4
0
Order By: Relevance
“…Comparing the FAs versus all the malignant lesions, 22 miRNAs showed significant deregulation. Among these, the most widely described as up-regulated in thyroid cancer are miR-146b-5b , miR-221 , miR-181 , and miR99b [ 10 , 11 , 13 ]; on the other hand, the most well-known downregulated miRNAs are miR144 , miR-451a , miR-497 , miR-195 , miR-143 , and miR-152 [ 13 ]. The analysis of enriched pathways showed that the 22 miRNAs deregulated in malignant RAS -positive thyroid tumors play a key role in several cancer-related pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing the FAs versus all the malignant lesions, 22 miRNAs showed significant deregulation. Among these, the most widely described as up-regulated in thyroid cancer are miR-146b-5b , miR-221 , miR-181 , and miR99b [ 10 , 11 , 13 ]; on the other hand, the most well-known downregulated miRNAs are miR144 , miR-451a , miR-497 , miR-195 , miR-143 , and miR-152 [ 13 ]. The analysis of enriched pathways showed that the 22 miRNAs deregulated in malignant RAS -positive thyroid tumors play a key role in several cancer-related pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Considering miR-144-3p , its overexpression inhibits proliferation, migration, and invasion of thyroid cancer cells in vitro [ 37 ]. Although the majority of reports found that miR-144-3p is downregulated [ 10 , 13 , 23 , 34 ], there are few studies reporting that miR-144-3p is overexpressed in thyroid cancer [ 38 , 39 ]; in one study, the overexpression of miR-144-3p was inversely correlated with the transcript quantity of the tumor suppressor gene PTEN [ 38 ]. In our study, miR-144-3p was significantly down-regulated in all the RAS -mutant malignant tumors compared to RAS -mutant FAs, therefore our report supports the evidence that miR-144-3p acts as a tumor suppressor miRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA encodes most of the non-coding genome. Mutations in RNA can cause many human diseases, including autoimmunity, or cancer [6].…”
Section: Introductionmentioning
confidence: 99%
“…Становится очевидным, что для повышения точности молекулярно-генетических тестов необходим поиск новых геномных изменений, высокоспецифичных для ФРЩЖ. В настоящее время во многом мутации и транслокации довольно хорошо изучены, при этом в ряде случаев их наличие или отсутствие не может считаться надежным диагностическим критерием дифференциальной диагностики, в связи с чем дальнейший поиск генетических маркеров для ФРЩЖ может быть направлен, например, на эпигенетические маркеры, такие как микроРНК [14].…”
Section: Introductionunclassified